Natural clay-based reusable piezo-responsive membrane for water droplet mediated energy harvesting, degradation of organic dye and pathogenic bacteria. (15th December 2022) - Mondal, Dhananjoy; Bardhan, Souravi; Das, Namrata; Roy, Jhilik; Ghosh, Saheli; Maity, Anupam; Roy, Shubham; Basu, Ruma; Das, Sukhen
Abstract: Nowadays, scientists have paid attention to utilizing natural and biocompatible materials for combating global challenges such as water pollution and the energy crisis. Moreover, pathogenic bacteria have also posed a severe threat to human health and the overuse of conventional antibiotics makes this situation even worse by evolving multidrug-resistant strains (MDR). Herein, we developed a natural clay (kaolinite) and multi-walled CNT (MWCNT) based nanocomposite, which has been encapsulated in the polymeric matrix of Poly (vinylidene fluoride-hexafluoropropylene) (PVDF-HFP) to achieve a multifunctional piezo-responsive membrane. This membrane is capable to generate piezoelectric energy under the perpendicular flow of water droplets. Such stimulus generates a 4.1 V voltage and 1.5 μA current maintaining a piezoelectric power density of 50 Wm −3 . It is worth noting that this membrane can eliminate around 96% Rhodamine-B concentration in only 60 min in water under ultrasound. A closer look suggests that the generation of reactive oxygen species (ROS), especially OH* accelerates the catalytic process under ultrasonic vibration. Such an interesting result motivated us to implement this piezocatalytic process to eradicate pathogenic bacteria, which shows a radical bactericidal effect (almost 99% killing) and evolves as an alternative antibacterial technique. Graphical Abstract: ga1 Highlights: Natural clay-modified MWCNT/kaolinite/PVDF membrane (PCK1) has been prepared. Synthesized membrane shows excellent piezo-response (50.7 pCN −1 ) and polarizability. Superior piezo-potential is found (4.1 V) when exposed to flowing water droplets. The piezocatalytic membrane exhibit 96% RhB degradation within 45 min of ultrasound. ROS-mediated E. coli eradication (99%) is found within 60 min of ultrasound.